Métamorphoses de l’université et parcours d’étudiants autochtones au Québec : enjeux d’accessibilité aux études et de persévérance scolaire dans une perspective de décolonisation de l’éducation - Jean-Luc Ratel; Annie Pilote (Recherches en Éducation)
In connection with the historical context of social segregation and the assimilative aim of formal education imposed on them, the Indigenous Peoples of Québec have long been excluded from higher education. Today, even if their graduation rates are increasing, a persistent gap with the non-Indigenous population is maintaining. The data in this article are drawn from twenty three interviews with students and university graduates of the First Nations of Québec, as part of a thesis in educational sciences. Our paper analyzes how these students manage to combine the contributions of Indigenous education with those of Western education and by developing paths that are part of the decolonization movement of education. Their relationship to Indigenous identity and cultures clearly influences their educational background and is analyzed taking into account power relations with the dominant culture. Our paper emphasizes more particularly the relationship to studies, the adaptation to the student profession and the balance between studies, work and family among Indigenous students, in a context of transition from university to multiversity which contributed to the increase of Indigenous university attendance.